Efficacy and safety of needle-free injection in patients with type 2 diabetes mellitus undergoing intensive insulin therapy: a randomized controlled trial based on the flash glucose monitoring system - Wang, Jing; Liu, Zibo; Jiao, Lijing; Zhou, Jing; Wang, Ting; Li, Caige; Wang, Qian; Yuan, Lingling; Zhang, Fang; Li, Guizhi; Zhu, Qiuxiao; Jin, Siyao; et al. (Frontiers in Endocrinology, 2026)
This randomized, open-label, parallel-controlled trial investigated the efficacy and safety of needle-free injection (NFI) compared to conventional insulin pen (CIP) in patients with type 2 diabetes mellitus (T2DM) undergoing intensive insulin therapy. A total of 64 hospitalized patients were randomly assigned to receive either NFI or CIP as part of a basal-bolus insulin regimen for 12 ± 2 days. Glycemic parameters were continuously monitored using a flash glucose monitoring (FGM) system. The NFI group showed significantly greater reductions in fasting plasma glucose (FPG) and 2-hour postprandial glucose (2hPPG), along with a more pronounced increase in serum 1,5-anhydroglucitol (1,5-AG) levels compared to the CIP group (all P < 0.05). Glycemic variability was also reduced in the NFI group, as indicated by higher time in range (TIR) and lower mean amplitude (MAGE) and largest amplitude (LAGE) of glycemic excursions (P < 0.05). Participants in the NFI group reached glycemic targets faster than those in the CIP group (1.88 ± 1.36 vs. 2.94 ± 1.59 days, P < 0.05), while daily insulin requirements remained comparable. Furthermore, the NFI group reported fewer injection-site adverse reactions, significantly lower pain scores, and higher treatment satisfaction (P < 0.001), with no increase in hypoglycemic events. These findings suggest that needle-free injection is a safe and effective alternative to conventional insulin delivery in hospitalized patients with T2DM, offering improved glycemic control, reduced glucose variability, and enhanced treatment experience.Clinical Trial Registrationidentifier ChiCTR1900022412.